School Principals’ Leadership Strategies in Enhancing Inclusive Teachers’ Competencies to Optimize Child Development - Irawati Fiantini; Moh. Rifa'i (Journal of Educational Management Research, 2026)
This study aims to analyze the role of school principals’ leadership strategies in enhancing teachers’ competencies to effectively manage inclusive learning. The research focuses on leadership approaches, academic supervision, teacher professional development, and collaboration with parents in supporting the development of children with special needs. A descriptive qualitative method was employed, conducted at an Islamic Integrated Early Childhood Education institution implementing inclusive education. Data were collected through participatory observation, in-depth interviews with the principal, regular teachers, special education teachers, and parents, as well as documentation analysis. The data were analyzed thematically using source triangulation to ensure validity. The findings reveal that principals’ leadership strategies significantly contribute to improving inclusive teachers’ competencies. The principal applied a combination of transformational and instructional leadership through academic supervision, technical guidance in lesson planning, constructive feedback, continuous professional training, and motivational practices such as appreciation and recognition. Furthermore, strong collaboration among teachers, special assistants, and parents strengthened the implementation of inclusive education. This study implies that adaptive, collaborative, and professional development–oriented leadership is essential for strengthening inclusive education practices and enhancing the capacity of school principals as instructional leaders and promoters of sustainable inclusive school culture.